A method for rapid pre-embedding of lithium in a negative electrode sheet of a lithium-ion battery

By using a reducing Li-aromatic hydrocarbon complex formed by a high polar solvent and a diluent on the negative electrode sheet of a lithium-ion battery, the problems of long prelithium time, poor ICE improvement and long cleaning time in the prior art are solved, and a more efficient prelithium process and better battery performance are achieved.

CN115425168BActive Publication Date: 2025-03-14SICHUAN JINMING ENTERPRISE MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211313376.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-24
Publication Date
2025-03-14
Estimated Expiration
2042-10-24

AI Technical Summary

Technical Problem

The existing pre-lithiation methods of lithium-ion batteries have problems such as long pre-lithium time, poor improvement in ICE of lithium batteries, and long cleaning time for pre-lithium pole sheets.

Method used

A reductive Li-aromatic hydrocarbon complex is formed in a mixed solvent of a high polar solvent and a diluent as a prelithiation reagent to achieve a locally highly concentrated Li-aromatic hydrocarbon complex, shortening the prelithium time of the electrode sheet and improving the ICE of the battery.

Benefits of technology

Effectively shorten the prelithium time of the electrode plate, improve the ICE of the battery, and shorten the cleaning time of the electrode plate, which is conducive to commercial-scale processing and improve production efficiency and maximize the protection of the battery's reversible capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115425168B_ABST
    Figure CN115425168B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of lithium-ion batteries, and is specifically a method for rapid pre-embedding of lithium in a negative electrode of a lithium-ion battery. The present invention prepares a mixed reagent of a high-polarity solvent and a diluent, and adds a diluent to a reducing Li-aromatic hydrocarbon complex solution to achieve local high concentration, so that more reducing Li-aromatic hydrocarbon complexes are attached to the pole piece, so that the pre-lithiation reagent of the mixed reagent and the Li-aromatic hydrocarbon complex can protect the lithium attached to the pole piece at a high concentration locally from being lost; it achieves a higher ICE at the same time, and a shorter time required for the same ICE, which can effectively shorten the pre-lithium time of the pole piece, improve the ICE of the battery, and the first cycle coulomb efficiency of the lithium half-cell can reach 99.11%; and shortens the cleaning time of the pole piece, which is conducive to commercial-scale processing to improve production efficiency and maximize the protection of the reversible capacity of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium-ion batteries, and relates to a method and mechanism for pre-embedding lithium in a negative electrode sheet, and specifically to a method for quickly pre-embedding lithium in a negative electrode sheet of a lithium-ion battery. Background Art

[0002] With the development of global industrial level, traditional fossil energy is becoming increasingly scarce. At the same time, due to the continuous increase in traditional energy consumption, environmental pollution problems are also becoming more and more serious. Therefore, the adjustment of energy structure has become a major challenge facing all countries.

[0003] The transition from fossil fuel vehicles to electric vehicles provides the possibility of building a new energy structure. Rechargeable battery technology is an important part of the popularization of electric vehicles, but its limited energy density can only provide a limited mileage for electric vehicles, limiting the transition from fossil fuel vehicles to electric vehicles and the adjustment of the energy structure.

[0004] At present, although lithium-ion battery technology is relatively advanced and mature in the market, there are still many defects to be improved, such as low first-cycle coulombic efficiency (ICE). The first-cycle coulombic efficiency refers to the ratio of the discharge capacity to the charge capacity of the battery during the first cycle. It is an important criterion for evaluating battery performance and determines the energy density of lithium-ion batteries. The widely used lithium-ion batteries currently have a reported first-cycle coulombic efficiency of about 90% due to their loss of active lithium in the first cycle. Pre-lithiation can effectively improve ICE by pre-doping additional lithium into the electrode before battery assembly to compensate for the loss of lithium during battery operation.

[0005] One method that is easy to process on a commercial scale is to mix the negative electrode with the consumed pre-lithiation reagent, however, this method will leave inactive residues in the battery. Compared with this commercial-scale processing method, another reported pre-lithiation method uses metallic lithium to react with bicyclic or polycyclic aromatic hydrocarbon compounds (such as naphthalene and biphenyl) in a polar solvent to generate a lithium compound solution with a strong reducing free radical anion, which is then reacted with the negative electrode material to achieve pre-lithiation. Chemical pre-lithiation uses a lithium-containing substance with a strong reducing property to reduce the negative electrode material through chemical or electrochemical means while replenishing lithium. The pre-lithiation compound can exist in the form of lithium ions in inorganic and organic salts in the solid interface film (SEI) on the surface of the negative electrode, or it can be a lithium insertion product (such as C6Li generated after graphite pre-lithiation), or a lithium alloy compound (such as Li-Si alloy product generated after silicon-based material pre-lithiation).

[0006] However, the known pre-lithiation methods still have many defects, such as long time consumption, difficulty in washing the residual aromatic hydrocarbon compounds on the surface of the pole piece, and great influence on the reversible capacity of the battery after pre-lithiation. The conventional pre-lithiation methods are summarized as follows:

[0007] Summary of the invention

[0008] In view of the above-mentioned existing problems or deficiencies, and in order to solve the problems of the existing lithium battery pre-lithiation methods, such as the long pre-lithiation time, poor improvement of the ICE of the lithium battery, and the long cleaning time of the electrode after pre-lithiation, the present invention provides a method for rapid pre-lithiation of the negative electrode of a lithium-ion battery, and a solution pre-lithiation mechanism. The present invention forms a reducing Li-aromatic hydrocarbon complex in a mixed solvent of a high-polarity solvent and a diluent as a pre-lithiation reagent, thereby achieving a locally high-concentration Li-aromatic hydrocarbon complex. This method can effectively shorten the pre-lithiation time of the electrode, improve the ICE of the battery, shorten the cleaning time of the electrode, and is conducive to commercial-scale processing to improve production efficiency and maximize the protection of the reversible capacity of the battery.

[0009] A method for rapid pre-embedding of lithium in a negative electrode sheet of a lithium battery, the specific steps are as follows:

[0010] Step 1: Pre-lithium reagent preparation:

[0011] With aromatic hydrocarbons as solutes and highly polar solvents (Li + Ether compounds with a positive ion complexation coefficient ≥ 2) and diluents (with Li + The complexation coefficient of the positive ion is <2) as the solvent, and a mixed solution with an aromatic hydrocarbon concentration of 0.1 to 1.2 mol / L is prepared; the solvent is calculated by volume, and the high polarity solvent: diluent is 1:0 to 6:1 (0 is not acceptable).

[0012] Then, lithium in a molar amount ≥ 1 times of the aromatic hydrocarbon is added to the mixed solution to prepare a pre-lithium solution.

[0013] Step 2: placing the negative electrode of the lithium-ion battery in the pre-lithium solution obtained in step 1 and reacting for 0.5 to 30 minutes to obtain a pre-lithium electrode.

[0014] Step 3: Clean the negative electrode of the lithium-ion battery that has been pre-lithiated in step 2 with a high-polarity solvent until there is no residue on the surface of the electrode, and then dry it completely under negative pressure.

[0015] Furthermore, the high polarity solvent is tetrahydrofuran, ethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 2-methyltetrahydrofuran and / or tetrahydropyran.

[0016] Furthermore, the diluents are cyclohexane, hexane, benzene, toluene, 1,4-dioxane, 1,3-dioxolane, n-pentane, cyclopentane, heptane, petroleum ether, dimethyldimethoxysilane, diethoxydimethylsilane, trimethylpropoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, tetraethyl silicate, propyltrimethoxysilane and / or propyltriethoxysilane.

[0017] Furthermore, the high polarity solvent used for cleaning in step 3 is the same as the high polarity solvent used in preparing the pre-lithium solution in step 1, so as to achieve a better cleaning effect.

[0018] The principle of rapid pre-lithiation in the present invention is: adding a diluent to the reducing Li-aromatic hydrocarbon complex solution to achieve local high concentration, more reducing Li-aromatic hydrocarbon complexes are attached to the electrode, and after rinsing, the aromatic hydrocarbon chemicals are dissolved in the rinsing bottle, and Li remains on the surface of the electrode and is embedded in the negative electrode material.

[0019] The principle of the pre-lithiation reaction is shown in reaction formula (1):

[0020]

[0021] When preparing the Li-aromatic hydrocarbon complex pre-lithiation reagent, the present invention prepares a mixed reagent of a high-polarity solvent and a diluent, and the mixed reagent and the Li-aromatic hydrocarbon complex pre-lithiation reagent can locally protect the lithium attached to the pole piece from being lost at a high concentration. On the other hand, it is easier to clean the pole piece after the pre-lithiation is completed than in the prior art, and the reversible capacity of the battery is protected, and the loss is less than that of the chemical pre-treatment method in the prior art.

[0022] In summary, compared with the existing pre-lithiation method, the present invention has a higher ICE at the same time and a shorter time required for the same ICE, which can effectively shorten the pre-lithiation time of the electrode and improve the ICE of the battery. The first-cycle coulomb efficiency of the lithium half-cell can reach 99.11%; and the electrode cleaning time is shortened, which is conducive to commercial-scale processing to improve production efficiency and maximize the protection of the reversible capacity of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Comparison of the first cycle coulombic efficiency of Example 1 at different pre-lithiation times with a solvent volume ratio of THF:cyclohexane=3:1;

[0024] Figure 2 Comparison of the first cycle coulombic efficiency of Example 1 at different pre-lithiation times with a solvent volume ratio of THF:cyclohexane=4:1;

[0025] Figure 3 Comparison of the first cycle coulombic efficiency of Example 1 at different pre-lithiation times with a solvent volume ratio of THF:cyclohexane=5:1;

[0026] Figure 4 This is a comparison chart of the first cycle coulombic efficiency of different solvent volume ratios at a pre-lithiation time of 5 min in Example 1;

[0027] Figure 5 This is a comparison chart of the first cycle coulombic efficiency of different solvent volume ratios at a pre-lithiation time of 7 min in Example 1;

[0028] Figure 6 This is a comparison chart of the first cycle coulombic efficiency of different solvent volume ratios at a pre-lithiation time of 10 min in Example 1;

[0029] Figure 7 This is a comparison chart of the first-cycle coulombic efficiency of Example 1 and the conventional pre-lithium method;

[0030] Figure 8 Schematic diagram of the local high-concentration pre-lithium solvent. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below with reference to the accompanying drawings and embodiments.

[0032] Example 1

[0033] Step 1, preparation of pre-lithium reagent. A mixed solution with a 4,4-dimethylbiphenyl concentration of 1 mol / L was prepared using aromatic hydrocarbon (4,4-dimethylbiphenyl) as solute, tetrahydrofuran (THF) as a highly polar solvent and cyclohexane as a diluent as solvent. The solvent volume ratio of THF: cyclohexane was 3:1, 4:1, 5:1, 1:0 respectively. After the solute was completely dissolved, lithium was added at a molar amount of 2 times that of 4,4-dimethylbiphenyl.

[0034] Step 2: Pre-lithiation electrode sheet: Insert the graphite negative electrode sheet (lithium-ion battery negative electrode sheet) into the folded stainless steel mesh, and then put it into the pre-lithium solution prepared in step 1 for 5 minutes, 7 minutes, 10 minutes, and 15 minutes to obtain the pre-lithium electrode sheet.

[0035] Step 3: Rinse the graphite negative electrode sheet pre-lithiated in step 2 in two bottles of tetrahydrofuran (THF) in turn until there is no residue on the surface of the graphite negative electrode sheet, and then completely dry the rinsed graphite negative electrode sheet under negative pressure conditions.

[0036] Step 4: Assemble the graphite negative electrode sheet dried in step 3 into a lithium half-cell, and test the assembled battery to read the first cycle charge and discharge data and calculate ICE. The electrolyte used is LB-002.

[0037] Example 2

[0038] Step 1, preparation of pre-lithium reagent. A mixed solution with a concentration of 1 mol / L of 4,4-dimethylbiphenyl is prepared using aromatic hydrocarbon (4,4-dimethylbiphenyl) as solute, tetrahydrofuran (THF) as high polarity solvent and cyclohexane as diluent as solvent. The solvent volume ratio of THF: cyclohexane is 3:1 and 1:0 respectively. After the solute is completely dissolved, lithium is added at a molar amount of 2 times that of 4,4-dimethylbiphenyl.

[0039] Step 2: Pre-lithiation electrode sheet: Insert the hard carbon negative electrode sheet (lithium-ion battery negative electrode sheet) into the folded stainless steel mesh, and then put it into the pre-lithiation solution prepared in step 1 for 15s, 30s, and 45s to obtain the pre-lithiation electrode sheet.

[0040] Step 3: rinse the hard carbon negative electrode sheet pre-lithiated in step 2 in two bottles of tetrahydrofuran (THF) in turn until there is no residue on the surface of the hard carbon negative electrode sheet, and then dry the rinsed hard carbon negative electrode sheet completely under negative pressure conditions.

[0041] Step 4: Assemble the hard carbon negative electrode sheet dried in step 3 into a lithium half-cell, and test the assembled battery to read the first cycle charge and discharge data and calculate ICE. The electrolyte used is LB-002.

[0042] Example 3

[0043] Step 1, preparation of pre-lithium reagent. A mixed solution with a 4,4-dimethylbiphenyl concentration of 1 mol / L was prepared using aromatic hydrocarbon (4,4-dimethylbiphenyl) as solute, ethylene glycol dimethyl ether as a highly polar solvent and n-pentane as a diluent as solvent. The solvent volume ratio of ethylene glycol dimethyl ether: n-pentane is 3:1, 1:0. After the solute is completely dissolved, lithium is added at a molar amount of 2 times that of 4,4-dimethylbiphenyl.

[0044] Step 2, pre-lithium electrode sheet. Insert the silicon oxide SOC negative electrode sheet (lithium-ion battery negative electrode sheet) into the folded stainless steel mesh, and then put it into the pre-lithium solution prepared in step 1 for 5 minutes, 10 minutes, and 15 minutes to obtain the pre-lithium electrode sheet.

[0045] Step 3: Rinse the silicon oxide SOC negative electrode sheet that has been pre-lithiated in step 2 in two bottles of ethylene glycol dimethyl ether in turn until there is no residue on the surface of the silicon oxide SOC negative electrode sheet, and then dry the rinsed silicon oxide SOC negative electrode sheet completely under negative pressure conditions.

[0046] Step 4: Assemble the silicon dioxide SOC negative electrode sheet dried in step 3 into a lithium half-cell, and test the assembled battery to read the first cycle charge and discharge data and calculate ICE. The electrolyte used is LB-046.

[0047] The control group of batteries was assembled in the same manner as in the example, except that the negative electrode plates were not pre-lithiated and the negative electrode plates were pre-lithiated using a conventional method.

[0048] The above embodiments and control groups were tested and analyzed as follows:

[0049] Figure 1 , Figure 2 , Figure 3 The graphite pole piece of Example 1 shows the change of ICE with pre-lithiation time under different solvent volume ratio conditions. At a constant rate of 0.1C, the ICE of the graphite pole piece in the first cycle of the battery with a solvent volume ratio of 5:1 increases with the increase of pre-lithiation time, and is close to 100% at around 7 minutes. The efficiency is improved by 10% compared with the control group. After pre-lithiation, the specific capacity of the battery decreases, and the decrease is most obvious at 15 minutes, which is 230.0mAh / g. The specific capacity of the battery is close to 270-300mAh / g after different pre-lithiation times from 5 minutes to 10 minutes.

[0050] Figure 4 , Figure 5 , Figure 6 The graphite pole piece of Example 1 changes with the solvent volume ratio ICE under different pre-lithiation time conditions. At a constant rate of 0.1C, as the proportion of cyclohexane gradually increases in the same time, the ICE of the battery increases and the specific capacity also increases. During the 5-minute pre-lithiation time, under the condition that the proportion of cyclohexane increases successively, the battery ICE increases from 97.35% to 100.83%, and the discharge specific capacity increases from 283.5mAh / g to 349.2mAh / g.

[0051] Figure 7 The graphite pole piece of Example 1 is compared with the conventional pre-lithiation method. The ICE achieved by the graphite pole piece after 5 minutes of pre-lithiation is close to that of the conventional pre-lithiation method after 10 minutes. The solvent volume THF: cyclohexane = 4:1 After 5 minutes of pre-lithiation, the pole piece specific capacity reaches 302.9mAh / g, while the conventional pre-lithiation method has a specific capacity of only 249.3mAh / g. The ICE achieved by Example 1 after 7 minutes of pre-lithiation is close to that of the conventional pre-lithiation method after 15 minutes. The solvent volume THF: cyclohexane = 4:1 After 7 minutes of pre-lithiation, the pole piece specific capacity reaches 322.9mAh / g, while the conventional pre-lithiation method has a specific capacity of only 238.9mAh / g. The comparison can prove that the present invention can effectively shorten the pre-lithiation time and protect the advantage of pole piece specific capacity.

[0052] Figure 8This is a schematic diagram of the local high concentration pre-lithium solvent of the present invention. The left figure is a molecular distribution diagram inside the pre-lithium solution at normal concentration, and the right figure is a molecular distribution diagram of the pre-lithium solution after adding cyclohexane to achieve local high concentration. It can be seen that the amount of Li-aromatic hydrocarbon complex formed is significantly increased in the pre-lithium solution that achieves local high concentration, and the distribution is more regular. The Li-aromatic hydrocarbon complex is divided by cyclohexane, which is beneficial to the attachment of the pole piece. After the active material attached to the pole piece increases, the pre-lithium effect of the pole piece is better, the first cycle ICE of the battery is higher, and the damage to the negative electrode material caused by the pre-lithium solution after adding cyclohexane is reduced.

[0053] The following tables give the parameters and test results of various embodiments:

[0054] Table 1 Graphite pole piece ICE under different pre-lithium conditions

[0055]

[0056] Table 2 Hard carbon pole piece ICE under different pre-lithium conditions

[0057]

[0058] Table 3 SOC pole piece ICE under different pre-lithium conditions

[0059]

[0060] It can be seen from the above embodiments that the present invention provides a pre-lithium solvent mechanism for quickly realizing pre-lithium embedding of negative electrodes, and a diluent cyclohexane is added to a reducing Li-aromatic hydrocarbon complex solution to achieve local high concentration. Compared with the control group, it can be seen that the first-cycle ICE efficiency of the battery is significantly improved. Compared with the reported pre-lithium methods, it effectively shortens the pre-lithium time of the pole piece, improves the ICE of the battery, shortens the pole piece cleaning time, and maximizes the protection of the reversible capacity of the battery. Based on this mechanism of the method of the present invention, the solvent can effectively pre-lithium the negative electrode materials (such as graphite, hard carbon and silicon dioxide), improve the first-cycle ICE of the battery, and achieve an increase in energy density.

Claims

1. A method for rapid pre-lithiation of a negative electrode sheet of a lithium-ion battery, characterized in that: The following steps are involved: Step 1: Pre-lithium reagent preparation: A mixed solution with an aromatic hydrocarbon concentration of 0.1 to 1.2 mol / L is prepared with aromatic hydrocarbon as solute, a high polarity solvent and a diluent as solvent; the solvent is calculated by volume, and the high polarity solvent: diluent is 1:0 to 6:1, and 0 is not selected; wherein the high polarity solvent refers to the solvent that reacts with Li + Ether compounds with a positive ion complexation coefficient ≥ 2, diluent refers to + The complexation coefficient of positive ions is less than 2; The diluent is cyclohexane, and the high polarity solvent is tetrahydrofuran; Then, lithium in a molar amount ≥ 1 times of the aromatic hydrocarbon is added to the mixed solution to prepare a pre-lithium solution; Step 2, placing the negative electrode of the lithium-ion battery in the pre-lithium solution obtained in step 1 to react for 0.5 to 30 minutes to obtain a pre-lithium electrode; Step 3: Clean the negative electrode of the lithium-ion battery that has been pre-lithiated in step 2 with a high-polarity solvent until there is no residue on the surface of the electrode, and then dry it completely under negative pressure.

2. The method for rapid pre-lithium insertion in a negative electrode sheet of a lithium-ion battery according to claim 1, characterized in that: The high polarity solvent used for cleaning in step 3 is the same as the high polarity solvent used in preparing the pre-lithium solution in step 1.

Citation Information

Patent Citations

  • Lithium element supplementing method for electrode of lithium ion battery

    CN103943825A

  • Lithiated silicon-based composite material as well as preparation method and application thereof

    CN111056555A